MONO- AND POLYPREDICATIVE UTTERANCES WITH THE SYNTACTIC MONO- AND POLYSYNONYMY OF MODERN FRENCH FICTION AS ASYMMETRIC COMPLEX LANGUAGE-DISCOURSE SIGNS - Lepetiukha, Anastasiia (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
In this article mono- and polypredicative utterances with the syntactic mono- and polysynonymy are considered as complex language-discourse signs in the dichotomy language – discourse from the standpoint of the mentalist concept of French linguist G. Guillaume who presented the causation of the language-discourse act in the form of the trine: mental operations → language → discourse. It was revealed that the secondary synonymic complex signs are formed within the space of the operating time of a thought movement as the result of the transformation of the primary syntagma / proposition based on sublinguistic schemes, or minimal units of mental information. It was proved that between systemic (linguistic) synonymic signs-transforms of one primary structure the asymmetry of semasiological meanings appears which causes the actualization of synonymic preferential options characterized by the asymmetry of semasiological and denotative meanings and by the explicit or implicit referential orientation in some co(n)text (linguistic and situational context) according to the communicative intention of the addressee. __________ REFERENCES • Benvenist, E. Slovar’ indoevropejskih social’nyh terminov [Dictionary of Indo-European terms]. Obshchaya lingvistika – General linguistics (Blagoveshchensk, 1998): 104–114 (in Russ.). • Giyom, Printsipy teoreticheskoy lingvistiki [Principles of theoretical linguistics] (Moskow, Editorial URSS 2004), 224 (in Russ.). • Minkin, L. M. «Nekotorye voprosy teorii yazyka i rechi [Some questions of language and speech].» Visnyk Kyivskoho natsionalnoho linhvistychnoho universytetu – Messanger of the Kiev National University3 (2) (2000): 15–25 (in Russ.). • Minkin, L. M., Shevchenko, I. S. «Nominaciya i referenciya v vyskazyvanii [Nomination and reference in the utterance].» Visnyk Kharkivskoho natsionalnoho universytetu im. V. Karazina. Seriia «Romano-hermanska filolohiia. Metodyka vykladannia inozemnykh mov» – Messanger of Kharkiv National University im. V. N. Karazina. "Series Romano-Germanic Philology. Methodology of teaching foreign languages" 66 (2005): 73–10 (in Russ.). • Minkin, L. M. «Aspekty kognitivno-lingvisticheskoj paradigmy [Aspects of the cognitive-linguistic paradigm].» Strukturno-semantychni i kohnityvno-dyskursyvni paradyhmy suchasnoho romanskoho movoznavstva: materialy Pershoi Vseukr. nauk. konf. romanistiv – Structural-semantic and cognitive-discursive paradigms of modern Romance linguistics: materials of the First All-Ukrainian Science conf. of romanists (Chernivtsi, 2006): 6–9 (in Russ.). • Мinkin,L. М. Teoriya lingvisticheskogo mentalizma G. Gijoma i voprosy nejrolingvistiki [G. Guillaume’s theory of linguistic mentalism and questions of neurolinguistics]. Visnyk Kyivskoho natsionalnoho linhvistychnoho universytetu – Messanger of Kyiv National Linguistic University 1 (2) (2012): 98–110 (in Russ.). • Boone, A., Joly, A. Dictionnaire terminologique de la systématique du langage (Paris, Harmattan, 1986), • Courbon, B. «Intégration syntagmatique du sens lexical et établissement de rapports synonymiques.» Synonymie (Paris, 2012): 329–342. • Doualan, G. «Introduction à une approche instrumentée de la synonymie. L’exemple du Dictionnaire Électronique des Synonymes du CRISCO.» Cahier du CRISCO 32 (Septembre 2011), 95. • Dubois, «Grammaire générative et transformationnelle.» Langue française1 (1963): 49–57. • Dubois, Grammaire structurale du français: nom et pronom (Paris, Larousse, 1965), 192. • Dubois, Dubois-Charlier, F. «Synonymie syntaxique et classification des verbes français.» Langages, La synonymie, 31ᵉ année, n°128 (1997): 51–71. • Gineste, M.-D. «De la phrase à la proposition sémantique: un point de vue de la psychologie cognitive du langage.» L’information grammaticale 98 (2003): 48–51. • Gross, Méthodes en syntaxe (Paris, Hermann, 1975), 414. • Guillaume, G. Temps et Verbe (Paris, Champion, 1965), 134. • Guillaume, G. Langage et science du langage (Paris, Librairie A. G. Nizet, Québec, Les presses de l’Université Laval, 1969), 288. • Lehmann, Martin-Berthet, F. Introduction à la lexicologie. Sémantique et morphologie (Paris, Nathan Université, 2003), 201. • Mel’čuk,A. «Paraphrase et lexique: la théorie Sens-Texte et le Dictionnaire explicatif et combinatoirе.» Dictionnaire explicatif et combinatoire du français contemporain. Recherches lexico-sémantiques (Montréal, 1992): 9–58. • Rossi, J.-G. Angèle Kremer Marietti, parcours philosophiques (Paris, Ellipses, 1997), 286. • Valin, R. «Introduction.» Leçons de linguistique de Gustave Guillaume 1948 – 1949. Structure sémiologique et structure psychique de la langue française. Série A. (Québec, Paris, 1971): 9–58. • Valin, R. Perspectives psychomécaniques sur ma syntaxe (Québec, Les presses de l’Université Laval, 1981), 96. • Valette, Linguistiques énonciatives et cognitives françaises, Gustave Guillaume, Bernard Pottier, Maurice Toussaint, Antoine Culioli (Paris, Honoré Champion, 2006), 316. SOURCES • Arnaud, G.-J. Le Commander enterre la hache (Рaris, Fleuve noir, 1997), 224. • Boileau-Narcejac Schuss (Paris, Denoёl, 1986), 204. • Gavalda, A. Je voudrais que quelqu’un m’attende quelque part (Paris, «J’ai lu», 1999), 159.